Photoacoustic Signal of Nanobubbles Induced in PEGylated Gold-Nanorod Colloid - Istas Pratomo Manalu (Piston: Journal of Technical Engineering, 2019)
We have developed a photoacoustic (PA) measurement system using a broadband ultrasonic transducer to detect the PA signals induced in a gold nanorod (GNRs) colloid irradiated by the nanosecond-pulsed laser beam. This study will investigate the PA signals of PEG-GNRs at longitudinal surface plasmon resonance. Several factors including aspect ratio of GNR, pulse energy, concentration, and wavelength are varied to investigate these effects on the PA signal. We show that at the certain condition the generated PA signal of PEG-GNRs stronger than uncoated GNRs. Moreover, the PA signals of PEG- GNRs are more stable than uncoated GNRs in the same condition.